PENGARUH KOMBINASI PUPUK KOMPOS JERAMI PADI DAN BIOCHAR SEKAM PADI TERHADAP SERAPAN N, P, K DAN HASIL TERUNG UNGU (SOLANUM MELONGENA L.) PADA TANAH ALUVIAL - Maudy, Melly; Hayati, Rita; Alhaddad, Abdul Mujib (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to determine the nutrient uptake of N, P and K from purple eggplant plants in alluvial soil. This research will take place from July – September 2023, carried out at the experimental field of the Faculty of Agriculture, Tanjungpura University, Pontianak City, West Kalimantan. This research used a Completely Randomized Design (CRD) with 6 treatments, namely: P0 = 0 (control); P1 = 100% rice straw; P2 = 100 rice husk biochar; and P3 = 75% rice straw compost + 25% rice husk biochar; P4 = 25% rice straw compost + 75% rice husk biochar; P5 = 50% rice straw compost + 50% rice husk biochar. Each treatment was repeated 4 times so there were 24 polybags. The variables observed in this study were the dry weight of the top of the plant, the uptake of N, P and K, the number of fruit per plant, the weight of the fruit per plant and the weight of the fruit per plant. The results of this study showed that the combination of rice straw compost and rice husk biochar had no significant effect on N, P and K uptake.